ARAH DAN KONSEP PENJAMINAN MUTU PENDIDIKAN ISLAM PERSPEKTIF RUSYDI AHMAD THOIMAH - Kholilur Rahman; Achmad Muhlis (STKIP Pesisir Selatan, 2025)
This study explores the direction and concept of quality assurance in Islamic education from the perspective of Rusydi Ahmad Thoimah. In his view, educational quality is not limited to academic achievement but represents a comprehensive process encompassing moral development, competence enhancement, and continuous institutional improvement. The research employed a library study with a descriptive qualitative approach. The data were thematically analyzed through reduction, presentation, and conclusion drawing. The findings indicate that Thoimah’s concept of Islamic education quality assurance highlights the integration of spiritual, intellectual, and social aspects. His holistic framework covers educational objectives, curriculum, teaching strategies, teachers, learners, and evaluation. This perspective aligns with modern quality assurance principles based on continuous quality improvement while remaining rooted in Islamic values. The novelty of this research lies in demonstrating the relevance of Thoimah’s thought to contemporary systems of Islamic education quality assurance. The study contributes theoretically to the discourse on Islamic education quality and practically to the implementation of quality standards in Islamic educational institutions.